2020
DOI: 10.1242/dev.193219
|View full text |Cite
|
Sign up to set email alerts
|

Ccn2a/Ctgfa is an injury-induced matricellular factor that promotes cardiac regeneration in zebrafish

Abstract: The ability of zebrafish to heal their heart after injury makes them an attractive model to investigate mechanisms governing the regenerative process. In this study, we show that the gene cellular communication network factor 2a (ccn2a), previously known as ctgfa, is induced in endocardial cells in the injured tissue and regulates CM proliferation and repopulation of the damaged tissue. We find that whereas in wild-type animals, CMs track along the newly formed blood vessels that revascularize the injured tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 77 publications
(81 reference statements)
1
28
1
Order By: Relevance
“…Similar to mammals, we found increased expressions of fn1a, fn1b, loxa, and tnc transcripts in AngII-induced zebrafish hearts, while spp1 expression remained unaltered. In contrast, our previous study identified ~15 fold increased expression of spp1 in injured zebrafish hearts [75]. These findings put forward that regulation of spp1 expression in cardiac fibrosis is context dependent.…”
Section: Discussioncontrasting
confidence: 65%
“…Similar to mammals, we found increased expressions of fn1a, fn1b, loxa, and tnc transcripts in AngII-induced zebrafish hearts, while spp1 expression remained unaltered. In contrast, our previous study identified ~15 fold increased expression of spp1 in injured zebrafish hearts [75]. These findings put forward that regulation of spp1 expression in cardiac fibrosis is context dependent.…”
Section: Discussioncontrasting
confidence: 65%
“…Secreted factors, including ECM proteins, have been shown to strongly influence CM regeneration after injury (53)(54)(55)(56). il11ra mutant hearts, after injury, display EndoMT-mediated fibrosis, a lack of transitional matrix deposition, and CM repopulation defects.…”
Section: Il-11 Signaling In Endothelial Cells Allows CM Repopulation After Cardiac Injurymentioning
confidence: 99%
“…Connective tissue growth factor (CTGF), also known as communication network factor 2a (Ccn2a), is a matricellular protein that is synthesized and secreted from endocardial cells after cardiac injuries (156). In zebrafish, CTGF has been reported necessary for heart regeneration by inducing cardiomyocyte proliferation and infiltration (156).…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…Connective tissue growth factor (CTGF), also known as communication network factor 2a (Ccn2a), is a matricellular protein that is synthesized and secreted from endocardial cells after cardiac injuries (156). In zebrafish, CTGF has been reported necessary for heart regeneration by inducing cardiomyocyte proliferation and infiltration (156). CTGF triggers cardiomyocyte cell cycle activity also in neonatal mammals (135), however, its potential impact on adult cardiomyocyte proliferation and heart regeneration has not been explored thus far.…”
Section: Extracellular Matrixmentioning
confidence: 99%